Preliminary Design of the Fusion Power Shutdown System Unit for ITER. (3rd April 2021) - Li, B.; Xia, Z. W.; Pan, Y. D.; Fang, T. Z.; Zhang, B.; Liu, S.; Li, W.; Yang, Y.; Kiss, G.; Maruyama, S.; Kruezi, U.; Liu, X. G.; et al.
Abstract: As an important part of the ITER gas injection system, the fusion power shutdown system delivers large quantities of gas into the vacuum vessel to stop the fusion power in an emergency case. Two identical but independent units are designed for mutual redundancy. Each unit includes an injection pipeline and a unit that contains a gas reservoir, solenoid valve, pneumatic isolation valve, and pressure switches. Among these components, the working gas reservoir parameters are investigated by experiments based on the required total gas quantity of at least 3000 Pa m 3 neon or mixtures of neon and hydrogen injected within 3 s. The working gas is released utilizing a pneumatically actuated valve that is not affected by the strong stray magnetic field of about 0.205 T. The associated solenoid valve is equipped with magnetic shielding that is designed by a magnetostatic analysis. These components lie on the same plane in the unit to maximize the maintainability. Furthermore, the structure integrity of the unit and its support frame is validated by a preliminary structural analysis.